Association between blood cadmium and depression varies by age and smoking status in US adult women: a cross-sectional study from NHANES 2005-2016 - Yewei Ji; Jinmin Wang (Komiyama Printing Co. Ltd, 2024)
Background: Cadmium, a toxic metal, is widely encountered in diverse environmental contexts. Despite its pervasive exposure, there is limited research on the association between blood cadmium levels and depression, especially among females. This study aimed to investigate the relationship between blood cadmium levels and depression in adult women. Methods: Data spanning 2005-2016 from the National Health and Nutrition Examination Survey (NHANES) were selected. Depression was diagnosed with the Patient Health Questionnaire (PHQ-9, score ≥10). Multiple logistic regression, multiple linear regression, and smoothed curve fitting were used to investigate the relationship between blood cadmium and depression. Subgroup analyses and interaction tests were performed to evaluate the stability of this association across populations. Results: A total of 1,173 individuals were diagnosed with depression. The heightened prevalence of depression was linked to increased blood cadmium levels, a trend that persisted even after quartering blood cadmium. In the fully adjusted model, each incremental unit of blood cadmium was associated with a 33% rise in the prevalence of depression (OR = 1.33, 95% CI: 1.21-1.45). Participants in the highest quartile were 63% more likely to experience depression compared to those in the lowest quartile of blood cadmium (OR = 1.63, 95% CI: 1.15-2.30), and PHQ-9 score increased by 0.73 (β = 0.73, 95% CI: 0.30-1.17). This positive association may be relevant to the general population. Conclusions: Blood cadmium levels are associated with depression in adult women, and this association varies by age and smoking status.